A combined digital image correlation/particle image velocimetry study of water-backed impact. (15th September 2019) - Zhang, Peng; Porfiri, Maurizio
Abstract: Several aeronautical and naval structures are routinely exposed to impulsive loading conditions that elicit complex fluid-structure interactions. An archetypal problem that has attracted considerable attention is the impact on a compliant plate, fixed on a water surface. Despite significant progress in mathematical modeling of the impact, several technical questions remain open due to the lack of a simultaneous experimental characterization of the structural response and fluid flow. Here, we seek to fill this gap of knowledge through the integration of digital image correlation (DIC) and particle image velocimetry (PIV). We employ DIC to measure the apparent in-plane displacement of the plate, from which we reconstruct its out-of-plane deflection. On the other hand, PIV is utilized to measure the velocity field of the water, from which we infer the pressure field in the fluid and the hydrodynamic loading on the plate. We examine a number of aggregated measures, including the mid-span deflection, strain energy stored in bending and stretching of the plate, modal contribution factors, hydrodynamic loading, and added mass coefficient. Just as our approach constitutes a significant methodological step forward in the study of unsteady fluid-structure interactions, our experimental results contribute new evidence for an improved understanding of water-backed impact.